Olga Benario em duas narrativas biográficas: da história para a ficção - Mendes, Giovana Oliveira (2014)
The present work constitutes a comparative study between two biographical novels, one of them belong to the category of non-fiction novel. The first, titled Olga Benario, is authored by the German writer Ruth Werner. The second, Olga, was written by the Brazilian journalist / writer Fernando Morais. The two texts, in their own way, try to reconstruct the life of one that became known as "the Jewish communist, mate of Luís Carlos Prestes, who had surrendered to Hitler by Vargas government." This study focuses on the analysis of these two biographies, both in relation to specific elements of the genre which they belong as to their content of historical nature, so that it is possible build relations between them, checking on which aspects they approach and on which are distant, and at which moments establish a dialogue with the actual fact. At the same time, it intends, at the end of the analysis, have an outlined image of the character Olga according to the Brazilian and German versions. Structurally, the dissertation is divided into three chapters, which are added to the introduction and final considerations. The first deals with some definitions of the biographical genre, as well as the particular characteristics of each of the novels in question, the second one is constituted of a brief contextualization of the period portrayed in the two biographies, from 1923 to 1942, with descriptions of some Brazilian journalists and historians about each epoch and confrontation with passages of literary texts. The third includes a comparative analysis of some passages from the writings of Werner and Morais, emphasizing the historical content, how the facts are narrated and the implicit social critique in discourse. Finally, the final considerations are presenting with the closing of the discussions proposed initially.